Organic chemistry in confining media - Todres, Zory Vlad (Springer International Publishing, 2013)
Zory Vlad Todres' monograph offers a fresh insight into an important and developed area of organic chemistry. Calixarene, cyclodextrins, and cucurbiturils as host molecules are well known, but the corresponding new and demonstrative publications deserve new exposition. This book principally widens our consideration of organic reactivity in confining media. Topics discussed include: effects of micellization, porous effects, effects of solvent cages, complexation to organometallic compounds, hydrogen-bond or charge-transfer complexation, sorption effects, effects of solvents, and stereochemical changes upon confinement. Organic Chemistry in Confining Media is useful for experienced organic chemists working in academia or industry, as well as chemists working in fields contiguous to organic chemistry.